Aquatic Salinization and Mangrove Species in a Changing Climate : Impact in the Indian Sundarbans - Mukhopadhyay, Anirban; Wheeler, David; Dasgupta, Susmita; Dey, Ajanta; Sobhan, Istiak (World Bank, Washington, DC, 2018)
This paper contributes to understanding the physical and economic effects of salinity diffusion and planning for appropriate adaptation for managing the Sundarbans in a changing climate, with a focus on the West Bengal portion of the tidal-wetland forest delta. A five-step analysis, using high-resolution spatial assessments, was conducted to get a broader picture of the migration of mangrove species with progressive aquatic salinization in a changing climate. A current (2015) basemap, with overlays of salinity tolerance for various mangrove species, and projected location-specific aquatic salinity for 2050 were used to predict the impacts of salinization on mangrove species by 2050. The results indicate patterns of gains and losses, with dominance of salt-tolerant species at the expense of freshwater species. Overall, the impact of salinity-induced mangrove migration will have an adverse effect on the flow of ecosystem services, ultimately impacting the livelihood options of poor households. Resources should be directed to developing alternative livelihoods for mangrove-dependent households. In addition, efforts are needed to develop sustainable policies that incorporate rising salinity, changes in mangrove dynamics, and the welfare impacts on poor communities.